Wanprestasi in the Murabahah Agreement: Juridical Analysis of Decision Number 1/Pdt.G.S/2022/PA. At the Religious Court of Appeal - Nurhisna Nurhisna; Mohammad Hipni; Busro Karim (Universitas Trunojoyo Madura, 2026)
This study examines the judicial reasoning underlying the resolution of a sharia economic dispute concerning breach of contract in a murabahah financing agreement, as reflected in Decision Number 1/Pdt.G.S/2022/PA.At. The research employs a normative juridical method using statutory and case approaches. Primary legal materials consist of the court decision and relevant Indonesian regulations governing Islamic finance, while secondary materials include scholarly literature on contract and Islamic commercial law. The findings reveal that the court declared the murabahah agreement legally valid and binding because it fulfilled both statutory requirements and sharia principles. The defendant was found to have committed a default by failing to perform contractual obligations despite prior warnings. The judgment demonstrates the integration of Indonesian civil law and Islamic legal principles, particularly pacta sunt servanda and al-wafā’ bi al-'uqūd (the obligation to honor contracts), in ensuring legal certainty and contractual justice. Furthermore, the decision illustrates that the enforcement of collateral constitutes a legitimate legal remedy in resolving Islamic financing disputes when conducted in accordance with contractual provisions and applicable legislation. The ruling reinforces the principles of legal certainty, fairness, and the protection of parties' rights within Indonesia's sharia economic dispute resolution system